Core-shell structure VO2 (M)-coated SiO2 powder as well as preparation and application thereof

VO2(M)@SiO2 powder is prepared through a simplified one-pot hydrothermal method of mixing silica sol and orange precursor solution, which solves the problems of complex and high cost of the existing process and achieves an efficient and low-energy consumption preparation process. , improving product performance and added value.

CN119350714APending Publication Date: 2025-01-24SHAANXI SCI TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411108629.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing VO2(M)@SiO2 preparation process is complex, difficult to control, high environmental pollution and energy consumption, and high cost, which limits its practical application in the field of smart windows.

Method used

A pot of water thermal method mixed with silicon -soluble and orange front -wheel drive solution, forms VO2 (B)@SiO2 powder through water heat reactions, and annealing in the presence of gas protection atmosphere and calcium oxide, obtaining a nuclear shell structure VO2 (M)@siO2 powder.

Benefits of technology

The preparation process is simplified, the energy consumption and environmental pollution are reduced, the control of the process is improved and the purity of the product, the phase variable performance and optical performance are enhanced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350714A_ABST
    Figure CN119350714A_ABST
Patent Text Reader

Abstract

The invention discloses VO2 (M) coated SiO2 powder with a core-shell structure as well as preparation and application of the VO2 (M) coated SiO2 powder. The preparation method comprises the following steps: mixing V2O5, urea and an oxalic acid aqueous solution to form a precursor solution A; mixing and dispersing the pre-diluted and dispersed silica sol B and the precursor solution A to obtain a mixture C; carrying out hydrothermal reaction on the mixture C, washing, centrifuging and drying to obtain VO2 (B) coated SiO2 powder; and annealing the VO2 (B) coated SiO2 powder in the presence of argon protective atmosphere and calcium oxide, cooling and grinding to obtain the core-shell structure VO2 (M) coated SiO2 powder. The method is short in process, low in energy consumption, narrow in thermal hysteresis loop width and high in visible light transmittance, and the phase change temperature and the sunlight modulation capacity are further adjusted through element doping. The core-shell structure VO2 (M) coated SiO2 powder prepared by the method can be used for preparing heat-insulating organic glass, a heat-insulating PMMA (polymethyl methacrylate) film and a heat-insulating PMMA coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of smart materials, and relates to a preparation method and application of VO2(M) powder, and in particular to a preparation method and application of VO2(M)@SiO2 powder with a core-shell structure. Background Art

[0002] In developing countries, building energy consumption accounts for 20-40% of primary energy consumption; in my country, this figure has reached 30%. With the acceleration of urbanization, this figure will continue to rise. 60% of building energy consumption is mainly used for heating, cooling, lighting and ventilation. Windows are the main channel for heat exchange between buildings and the outside world. It is estimated that about 50% of heat exchange is carried out through windows. In order to improve the energy-saving effect of windows, reduce energy consumption and implement the concept of sustainable development, the use of high-performance energy-saving glass is one of the effective ways.

[0003] Rutile M1 / R phase VO2 material undergoes a primary structural phase transition at around 68°C. At low temperatures (T<68°C), it is in a monoclinic semiconductor state, allowing most near-infrared light to pass through; at high temperatures (T>68°C), it is in a tetragonal metallic state, with high resistance to near-infrared light (reflection and absorption). Utilizing this characteristic, it can be coated on the surface of building glass to block most of the near-infrared light in solar radiation in summer, reduce indoor temperature, and reduce cooling energy consumption; in winter, near-infrared solar heat can be allowed to pass through, maintaining indoor temperature and reducing heating energy consumption, so as to achieve energy saving. However, in actual application scenarios, due to the relatively high refractive index of VO2, its transmittance in the visible light band is low, and VO2's antioxidant ability and weather resistance are also relatively poor, so the actual application of VO2 in the field of smart windows is still greatly limited. Literature reports that SiO2 has a low refractive index, and compounding with VO2 or forming a core-shell structure can improve the optical properties of VO2, enhance its antioxidant properties, and change its thermally induced back-loop width. At present, the preparation process of VO2(M)@SiO2 is through the hydrolysis and condensation of tetraethyl orthosilicate (TEOS), and then adding surfactant modification for VO2(M) coating. This method has a complicated preparation process and relatively difficult process control. It uses a large amount of anhydrous ethanol, which causes high environmental pollution and energy consumption. In addition, the price of TEOS is very high, and the modification cost is relatively high, which limits its application. Summary of the invention

[0004] The purpose of the present invention is to provide a VO2(M)@SiO2 powder, a preparation method and its application which have simple and easy-to-control process, short flow and low energy consumption. Moreover, the method has low cost and little environmental pollution. The prepared VO2(M)@SiO2 powder has excellent phase change properties and optical properties.

[0005] The objectives of the present invention are achieved through the following technical solutions.

[0006] In one aspect, the present invention provides a method for preparing a core-shell structured VO2(M)@SiO2 powder, comprising the following steps:

[0007] 1) Preparation of silica sol gel coated VO2 (B):

[0008] 1a) adding (1-3) parts of V2O5 and (0.18-0.20) parts of urea to (130-150) parts of oxalic acid aqueous solution at room temperature and under stirring to form a precursor solution A;

[0009] 1b) pre-dilute and disperse (4-8) parts of anhydrous ethanol and (3-6) parts of silica sol at room temperature and at a stirring speed to obtain pre-diluted dispersed silica sol B;

[0010] 1c) mixing and dispersing (7-14) parts of the pre-diluted dispersed silica sol B and (132-154) parts of the precursor solution A at room temperature and at a stirring speed to obtain a mixture C;

[0011] 1d) subjecting the mixture C to a hydrothermal reaction, and the hydrothermal material is repeatedly washed and centrifuged, and then dried, to obtain VO2(B)@SiO2 powder coated with VO2(B) by silica sol gelation;

[0012] 3) The silica sol gel-coated VO2(B)@SiO2 powder is annealed in an argon protective atmosphere and in the presence of calcium oxide, cooled to room temperature and then ground to obtain core-shell structured VO2(M)@SiO2 powder.

[0013] Preferably, in step 1), the rotation speed is 300-500 r / min.

[0014] Preferably, the mass concentration of the oxalic acid aqueous solution is 2.5-3.5%.

[0015] Preferably, anhydrous ethanol and silica sol are pre-diluted and dispersed for 30-60 minutes.

[0016] Preferably, the pre-diluted dispersed silica sol B is mixed and dispersed with the precursor solution A for 4-8 hours.

[0017] Preferably, the mixture C is subjected to a hydrothermal reaction at 200-220° C. for 24-36 hours, the material on the wall of the hydrothermal reactor is removed, washed and centrifuged repeatedly for 3-5 times, and dried at 60-80° C. for 8-12 hours.

[0018] Preferably, the amount of calcium oxide used is 3-5 times the mass of the silica sol gel-coated VO2(B); and the annealing treatment is performed at 600-800°C for 6-8h.

[0019] In another aspect of the present invention, a core-shell structure VO2(M)@SiO2 powder prepared by the method is provided.

[0020] In another aspect, the present invention provides a method for preparing heat-insulating organic glass, heat-insulating PMMA film and heat-insulating PMMA coating using core-shell structure VO2(M)@SiO2 powder, comprising:

[0021] 1 part of PMMA slurry containing VO2(M)@SiO2 is mixed with (1-2) parts of methyl methacrylate MMA prepolymer slurry, polymerized at 55-62°C for 2-4h, heated to 80-120°C, and kept warm for 30-120min.

[0022] Preferably, the PMMA slurry containing VO2(M)@SiO2 is prepared by dissolving, dispersing and grinding (0.09-0.12) parts of VO2(M)@SiO2, (0.9-1.2) parts of PMMA molding powder and (3-6) parts of triethyl phosphate.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] 1) The present invention adopts a one-pot hydrothermal method of mixing silica sol and orange precursor solution. The hydrothermal reaction formation process of VO2(B) and the gelation of silica sol are carried out simultaneously, thereby eliminating the alcoholysis step and the VO2(B) separation and purification step. The preparation process is simpler and easier to control, the process is shorter, the energy consumption is lower, the environmental pollution is less, and the production cost is lower.

[0025] 2) The present invention adopts the dual effects of argon protective atmosphere and calcium oxide conversion of water, which can effectively avoid the oxidation effect of water removed from silica gel on VO2(B / M) during the annealing process, and prepares VO2(M)@SiO2 with higher purity, lower phase transition temperature, narrower thermal hysteresis loop width and better optical performance.

[0026] 3) The present invention adopts triethyl phosphate as the solvent for PMMA molding powder and the grinding and dispersing medium for VO2(M)@SiO2, which can not only dissolve PMMA molding powder and serve as the grinding and dispersing medium for VO2(M)@SiO2, but also increase the toughness of thermal insulating organic glass, thermal insulating PMMA film and PMMA coating, and also give the thermal insulating organic glass, thermal insulating PMMA film and PMMA coating excellent flame retardant properties.

[0027] The prepared thermal insulation organic glass, thermal insulation PMMA film and thermal insulation PMMA coating have good transparent thermal insulation performance, can expand the application scope of organic glass, PMMA film and PMMA coating, and enhance their application added value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0029] Figure 1 TEM diffraction pattern of (VO2@SiO2) particles prepared in Example 1;

[0030] Figure 2 This is a scanning electron microscope (SEM) image of the (VO2@SiO2) particles prepared in Example 1;

[0031] Figure 3 XRD spectrum of (VO2@SiO2) particles prepared in Example 1;

[0032] Figure 4 This is a comparison diagram of the DSC curves of the (VO2@SiO2) particles prepared in Example 1;

[0033] Figure 5 This is the optical transmittance diagram of the (VO2@SiO2) particles prepared in Example 1. DETAILED DESCRIPTION

[0034] The invention is further described in detail below in conjunction with the embodiments, but it is not intended to limit the invention in any way.

[0035] The embodiment of the present invention provides a method for preparing a core-shell structured VO2(M)@SiO2 powder, comprising:

[0036] Step 1, preparation of silica sol gel coated VO2 (B):

[0037] 1a) adding (1-3) parts of V2O5 and (0.18-0.20) parts of urea to (130-150) parts of an aqueous solution of oxalic acid having a mass concentration of 2.5-3.5% at room temperature and stirring at 300-500 r / min to form an orange precursor solution A;

[0038] 1b) pre-dilute and disperse (3-6) parts of silica sol for 30-60 minutes at room temperature and 300-500 r / min stirring conditions, using (4-8) parts of anhydrous ethanol as a dispersing medium to obtain pre-diluted dispersed silica sol B;

[0039] 1c) mixing and dispersing (7-14) parts of the pre-diluted dispersed silica sol B and (132-154) parts of the orange precursor solution A at room temperature and 300-500 r / min stirring for 4-8 hours to obtain a dark blue or dark green mixture C;

[0040] 1d) The dark blue or dark green mixture C is transferred to a polytetrafluoroethylene hydrothermal reactor, and the hydrothermal reaction is carried out at 200-220°C for 24-36 hours. The material on the wall of the hydrothermal reactor is removed, and the material is repeatedly washed and centrifuged for 3-5 times, and dried at 60-80°C for 8-12 hours to obtain silica sol gel-coated VO2(B) powder, i.e., VO2(B)@SiO2 powder.

[0041] Step 2: anneal the silica sol gel-coated VO2(B) at 600-800°C for 6-8h in an argon protective atmosphere and in the presence of calcium oxide, cool to room temperature and grind to obtain core-shell structured VO2(M)@SiO2 powder.

[0042] By optimizing the ratio between the orange precursor solution A in step 1a) and the pre-diluted dispersed silica sol B in step 1b), a better SiO2 layer thickness and SiO2 layer density can be obtained, thereby giving VO2(M) better phase change properties and optical properties.

[0043] The orange precursor solution A prepared in step 1a) is mixed and dispersed with the pre-diluted dispersed silica sol B obtained in step 1b) to obtain a dark blue or dark green mixture C. During the hydrothermal reaction, the orange precursor solution A undergoes an in-situ hydrothermal reaction to prepare VO2(B); at the same time, the pre-diluted dispersed silica sol B is gelled in-situ to generate silica gel. The hydrothermal reaction and gelation are carried out simultaneously. The obtained VO2(B)@SiO2 powder has a small and uniform particle size. The VO2(M)@SiO2 powder obtained by further annealing has a small and uniform particle size. This can effectively alleviate the problem of easy agglomeration of VO2(B)@SiO2 or VO2(M)@SiO2 prepared by the prior art of first preparing VO2(B) or VO2(M) and then degelling the VO2(B)@SiO2 with ethyl silicate.

[0044] The preparation process of core-shell structure VO2(M)@SiO2 powder is further illustrated by different examples below.

[0045] Example 1

[0046] 1) Preparation of silica sol gel coated VO2 (B):

[0047] 1a) 1 part of V2O5 and 0.19 parts of urea were sequentially added to 140 parts of 2.5% oxalic acid aqueous solution at room temperature and 300 r / min stirring to form an orange precursor solution A;

[0048] 1b) Under stirring conditions of 300 r / min at room temperature, using 6 parts of anhydrous ethanol as a dispersing medium, pre-dilute and disperse 3 parts of silica sol for 40 minutes to obtain pre-diluted dispersed silica sol B;

[0049] 1c) Mix 10 parts of pre-diluted dispersed silica sol B with 132 parts of orange precursor solution A under stirring at room temperature and 300 r / min for 4 h to obtain a dark blue or dark green mixture C;

[0050] 1d) The dark blue or dark green mixture C is transferred to a polytetrafluoroethylene hydrothermal reactor and subjected to a hydrothermal reaction at 200°C for 36 hours. The material on the wall of the hydrothermal reactor is removed, washed and centrifuged repeatedly for 3 times, and dried at 70°C for 10 hours to obtain silica sol gel-coated VO2(B) powder, i.e., VO2(B)@SiO2 powder.

[0051] 2) The silica sol gel coated VO2(B) was annealed at 600°C for 8 h in an argon protective atmosphere and in the presence of calcium oxide, and then ground to obtain core-shell structured VO2(M)@SiO2 powder.

[0052] Example 2

[0053] 1) Preparation of silica sol gel coated VO2 (B):

[0054] 1a) 3 parts of V2O5 and 0.18 parts of urea were added to 150 parts of 3% oxalic acid aqueous solution at room temperature and 400 r / min stirring to form an orange precursor solution A;

[0055] 1b) Under the stirring condition of 400 r / min at room temperature, using 8 parts of anhydrous ethanol as the auxiliary dispersion medium, 5 parts of silica sol were pre-diluted and dispersed for 60 minutes to obtain pre-diluted dispersed silica sol B;

[0056] 1c) Mixing and dispersing 14 parts of pre-diluted dispersed silica sol B with 154 parts of orange precursor solution A at room temperature and 400 r / min stirring for 8 h to obtain a dark blue or dark green mixture C;

[0057] 1d) The dark blue or dark green mixture C is transferred to a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 220°C for 24 hours. The material on the wall of the hydrothermal reactor is removed, washed and centrifuged repeatedly for 4 times, and dried at 80°C for 8 hours to obtain silica sol gel-coated VO2(B) powder, i.e., VO2(B)@SiO2 powder.

[0058] 3) The silica sol gel coated VO2(B) was annealed at 800°C for 6 hours in an argon protective atmosphere and in the presence of calcium oxide, and then ground to obtain core-shell structured VO2(M)@SiO2 powder after cooling to room temperature.

[0059] Example 3

[0060] 1) Preparation of silica sol gel coated VO2 (B):

[0061] 1a) 2 parts of V2O5 and 0.20 parts of urea were added to 130 parts of 3.5% oxalic acid aqueous solution in sequence under stirring at room temperature and 500 r / min to form an orange precursor solution A;

[0062] 1b) Under the stirring condition of 500 r / min at room temperature, using 4 parts of anhydrous ethanol as the auxiliary dispersion medium, 6 parts of silica sol were pre-diluted and dispersed for 30 minutes to obtain pre-diluted dispersed silica sol B;

[0063] 1c) Mix 7 parts of pre-diluted dispersed silica sol B with 144 parts of orange precursor solution A under stirring at room temperature and 500 r / min for 6 h to obtain a dark blue or dark green mixture C;

[0064] 1d) The dark blue or dark green mixture C is transferred to a polytetrafluoroethylene hydrothermal reactor and subjected to a hydrothermal reaction at 210°C for 30 h. The material on the wall of the hydrothermal reactor is removed, washed and centrifuged repeatedly for 5 times, and dried at 60°C for 12 h to obtain silica sol gel-coated VO2(B) powder, i.e., VO2(B)@SiO2 powder.

[0065] 4) The silica sol gel coated VO2(B) was annealed at 700°C for 7h in an argon protective atmosphere and in the presence of calcium oxide, cooled to room temperature and then ground to obtain core-shell structured VO2(M)@SiO2 powder.

[0066] The effect of the present invention can be Figure 1-5 see:

[0067] from Figure 1 It can be seen that the prepared powder material has an obvious core-shell structure, with the core layer being about several hundred nanometers and the shell layer being several tens of nanometers.

[0068] from Figure 2 It can be seen that the prepared powder material particles are relatively uniform and spherical.

[0069] from Figure 3 It can be seen that the prepared powder material is VO2(M)@SiO2.

[0070] from Figure 4 It can be seen that the phase transition temperature of the prepared powder material VO2(M)@SiO2 is lower than that of VO2(M), and the width of the thermal hysteresis loop is narrowed.

[0071] from Figure 5 It can be seen that the solar transmittance of the prepared powder material VO2(M)@SiO2 is significantly improved compared with VO2(M), with the improvement being close to 100%.

[0072] It can be seen from the above examples that the VO2(M)@SiO2 prepared in this example is uniformly spherical and has an obvious core-shell structure; the phase transition temperature is 1-3°C lower than VO2(M), the width of the thermal hysteresis loop is narrowed to 6-8°C, and the solar transmittance is about 30% higher than VO2(M).

[0073] Furthermore, the core-shell structure VO2(M)@SiO2 powder prepared by the present invention can be used to prepare thermal insulation plexiglass, thermal insulation PMMA film and thermal insulation PMMA coating, by mixing 1 part of PMMA slurry containing VO2(M)@SiO2 with (1-2) parts of methyl methacrylate MMA prepolymer slurry, bulk polymerization at 55-62°C for 2-4h, and treatment at 80-120°C for 30-120min.

[0074] The PMMA slurry containing VO2(M)@SiO2 is prepared by dissolving, dispersing and grinding (0.09-0.12) parts of VO2(M)@SiO2, (0.9-1.2) parts of PMMA molding powder and (3-6) parts of triethyl phosphate.

[0075] The preparation of heat-insulating organic glass includes: mixing 1 part of PMMA slurry containing VO2(M)@SiO2 with 2 parts of methyl methacrylate MMA prepolymer slurry, bulk polymerization at 62°C for 4 hours, and treatment at 120°C for 120 minutes.

[0076] The PMMA slurry containing VO2(M)@SiO2 is 0.12 parts of VO2(M)@SiO2, 1.1 parts of PMMA molding powder, and 5 parts of triethyl phosphate.

[0077] The method comprises the following steps: mixing one part of PMMA slurry containing VO2(M)@SiO2 and one part of methyl methacrylate (MMA) prepolymer slurry, performing bulk polymerization at 55° C. for 3 hours, and treating at 80° C. for 60 minutes.

[0078] The PMMA slurry containing VO2(M)@SiO2 is 0.10 parts of VO2(M)@SiO2, 0.9 parts of PMMA molding powder, and 3 parts of triethyl phosphate.

[0079] The heat-insulating PMMA coating is prepared, comprising: mixing 1 part of PMMA slurry containing VO2(M)@SiO2 with 1.5 parts of methyl methacrylate MMA prepolymer slurry, bulk polymerizing at 60°C for 2 hours, and treating at 100°C for 30 minutes.

[0080] The PMMA slurry containing VO2(M)@SiO2 is 0.09 parts of VO2(M)@SiO2, 1.2 parts of PMMA molding powder, and 6 parts of triethyl phosphate.

[0081] Experimental measurements have shown that the use of VO2(M)@SiO2 powder to prepare thermal insulating plexiglass, thermal insulating PMMA films and thermal insulating PMMA coatings can increase the toughness of the thermal insulating plexiglass, thermal insulating PMMA films and PMMA coatings, and can also give the thermal insulating plexiglass, thermal insulating PMMA films and PMMA coatings excellent flame retardant properties.

[0082] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing a core-shell structured VO2(M)@SiO2 powder, characterized in that: The steps include: 1) Preparation of silica sol gel coated VO2 (B): 1a) adding (1-3) parts of V2O5 and (0.18-0.20) parts of urea to (130-150) parts of oxalic acid aqueous solution at room temperature and under stirring to form a precursor solution A; 1b) pre-dilute and disperse (4-8) parts of anhydrous ethanol and (3-6) parts of silica sol at room temperature and at a stirring speed to obtain pre-diluted dispersed silica sol B; 1c) mixing and dispersing (7-14) parts of the pre-diluted dispersed silica sol B and (132-154) parts of the precursor solution A at room temperature and at a stirring speed to obtain a mixture C; 1d) subjecting the mixture C to a hydrothermal reaction, and the hydrothermal material is repeatedly washed and centrifuged, and then dried, to obtain VO2(B)@SiO2 powder coated with VO2(B) by silica sol gelation; 2) The silica sol gel-coated VO2(B)@SiO2 powder is annealed in an argon protective atmosphere and in the presence of calcium oxide, cooled to room temperature and then ground to obtain core-shell structured VO2(M)@SiO2 powder.

2. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: In step 1), the rotation speed is 300-500r / min.

3. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: The mass concentration of the oxalic acid aqueous solution is 2.5-3.5%.

4. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: Anhydrous ethanol and silica sol are pre-diluted and dispersed for 30-60 minutes.

5. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: The pre-diluted dispersed silica sol B is mixed and dispersed with the precursor solution A for 4-8 hours.

6. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: The mixture C is subjected to a hydrothermal reaction at 200-220° C. for 24-36 hours, the material on the wall of the hydrothermal reactor is removed, washed and centrifuged repeatedly for 3-5 times, and dried at 60-80° C. for 8-12 hours.

7. The method for preparing the core-shell structure VO2(M)@SiO2 powder according to claim 1, characterized in that: The amount of calcium oxide used is 3-5 times the mass of silica sol gel-coated VO2(B); annealing treatment is carried out at 600-800℃ for 6-8h.

8. A core-shell structured VO2(M)@SiO2 powder prepared by the method according to any one of claims 1 to 7.

9. A method for preparing heat-insulating organic glass, heat-insulating PMMA film and heat-insulating PMMA coating using the core-shell structure VO2(M)@SiO2 powder according to claim 8, characterized in that: include: 1 part of PMMA slurry containing VO2(M)@SiO2 is mixed with (1-2) parts of methyl methacrylate MMA prepolymer slurry, polymerized at 55-62°C for 2-4h, and heated to 80-120°C and kept warm for 30-120min.

10. The method for preparing heat-insulating organic glass, heat-insulating PMMA film and heat-insulating PMMA coating according to claim 9, characterized in that: The PMMA slurry containing VO2(M)@SiO2 is prepared by dissolving, dispersing and grinding (0.09-0.12) parts of VO2(M)@SiO2, (0.9-1.2) parts of PMMA molding powder and (3-6) parts of triethyl phosphate.